Coronary Artery Disease: A Descriptive Analysis of Risk Factors: Before and After Treatment - Dinkar, S; Rao, Suresh; Vakamudi, M; Saldanha, R; Balakrishnan, KR (National Journal of Community Medicine, 2010)
With the increasing life span of man, the number of ageing people is also increasing, and along with that the number of diseases affecting them is also increasing. Atherosclerotic coronary artery disease is one of them. Coronary revascularization was started in 1960s through the pioneering efforts of David Sabiston and Kolessov. This is a retrospective descriptive study. A total number of 1050 Patients were operated on beating heart surgery from 1998 to Nov. 2002 out of which 852 patients were analysed to know the results and prognostic outcomes. Mean age was 57.8 years (range 31 - 80years) with M:F ratio of 7:1. The pre-operative parameters studied were DM, HTN, hyperlipidemia, family history of CAD, smoking and past history of MI. other parameters included pulmonary disease, chronic renal failure, CVA, APD, PVD etc. 55.75% patients were diabetic, 53.99% were hypertensive and 24.4% had history of hyperlipidemia. Family history was positive in 12.9% of the patients, 25% were smokers and 44% had history of previous MI. average number of diseased vessels was 2.34 with triple vessel disease being most common. 6.6% had history of pulmonary diseases, 7.4% had pre-operative renal failure and 2% had past history of CV stroke. Overall, in-hospital mortality was 1.4%. relative risk for mortality, morbidity, new onset of renal failure, CVA, arrhythmias, CCF were calculated. Mean hospital stay was 9.83days (range 6 - 41years), mean ICU stay was 74.3 hours (range 73 - 700years). Usage of blood and blood products was significantly less. Freedom from complications was 93%. LVEF<40%, age >70 years, high diastolic PA pressure> 15mm Hg were found to be significant risk factors for mortality. Females were found to be 2.6 times more at risk for mortality and development of complications as compared to males. Patients with previous history of MI were found to be more at risk of developing complications increasing their hospital and ICU stay.